2022
DOI: 10.14740/jh984
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Survival of Extra Nodal Diffuse Large B-Cell Lymphoma and Comparison With Gastrointestinal Diffuse Large B-Cell Lymphoma

Abstract: Background Diffuse large B-cell lymphoma (DLBCL) constitutes 30% of all non-Hodgkin’s lymphomas. It can present as a nodal disease or as an extra nodal disease. Based on the site of origin, extra nodal DLBCL (EN-DLBCL) may have a distinct clinical outcome. Apart from the site of origin, factors including demographics, stage, and presence of any other primary malignancy also affect the outcome. The purpose of our study was to characterize prognostically distinct groups based on the site of presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Higher mortality was observed in White patients and in patients with late presentation and a history of second malignancies. In comparison to intestinal tract DLBCL, a disease involving CNS, pancreas, and the respiratory system was associated with worse survival [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher mortality was observed in White patients and in patients with late presentation and a history of second malignancies. In comparison to intestinal tract DLBCL, a disease involving CNS, pancreas, and the respiratory system was associated with worse survival [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presentation described today is not often seen [2][3] and is considered a high-grade lymphoma [4][5]. Of all forms of DLBCL, extranodal forms only comprise 34.48% [10]. The gastrointestinal tract has been noted to be the most common extranodal site [8].…”
Section: Discussionmentioning
confidence: 99%
“…Rare sites of extranodal DLBCL have been documented in the literature, including presentations in the scalp, testicles, bone, bladder, and nasal septum [2][3][6][7][8][9]. A recent 2022 study found that the percentages of extranodal DLBCL from years 2000-2015 at the age of 18 or greater in their search were as follows: GI tract 28.31%, nervous system 13.78%, head and neck 11.79%, skin and soft tissue 9.54%, genitourinary 7.24%, musculoskeletal 5.80%, respiratory tract 5.17%, pancreas and hepatobiliary 4.16%, endocrine organs 3.66%, heart and mediastinum 3.28%, breast 2.49%, bone marrow 2.47%, and others 2.30% [10]. Extranodal DLBCL was found to be more common in non-Hispanic white males 60 years of age or older [10].…”
Section: Discussionmentioning
confidence: 99%
“…[4,5]. Among these extranodal sites, the GI tract is the most commonly involved site, especially the stomach in 65%, the small intestine in 20-35%, and the colon and rectum in 5-15% [6]. Typically, these patients present with gastrointestinal (GI) symptoms like abdominal pain, nausea, vomiting, weight loss, diarrhea, and rarely, can present as acute complete or partial bowel obstructions.…”
Section: Discussionmentioning
confidence: 99%